Effect of long-term strenuous training on the plasma phospholipid fatty acid composition in handball players - Arsić, Aleksandra; Petrović, Snježana; Čikiriz, Nikola; Ristić Medić, Danijela; Vučić, Vesna (Vojnosanitetski pregled, 2021)
Background/Aim. Consensus on the exercise effect on the fatty acid metabolism has not been reached, and probably depends on the type of sports (aerobic, anaerobic or mixed). The aim of this study was to investigate effect of long-term handball training on the body composition, lipid profile and the plasma phospholipid fatty acid composition in female and male younger players. Methods. Seventeen female and 15 male active handball players, aged 16–20 years, who competed at the national/international level, were enrolled in the study. A control group was established from healthy, sedentary individuals (13 females and 19 males, aged 17–21 years), comparable to the athletes in terms of age, sex and body mass index. Results. In both groups of handball players a higher percentage of palmitoleic acid and alpha linolenic acid (18:3, n-3), were found and lower percentage of oleic acid and docosahexaenoic acid (22:6, n-3), when compared with corresponding control group. On the other hand, the lower level of stearic acid and estimated activity of plasma elongase was detected in female players than in sedentary women. Furthermore, higher proportion of linoleic acid (18:2, n-6), n-6 polyunsaturated fatty acids (PUFA) and total PUFA was found only in female players in comparison to the control group. Conclusion. The observed differences between handball players and sedentary individuals showed that handball training influenced lipid and fatty acid metabolism. Follow-up of these changes could indicate potential need for supplementation or nutritional intervention in young handball players.
Keywords: body composition; lipid metabolism; fatty acids; sports; sex factors